2021
DOI: 10.3390/pathogens10091198
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequencing of Leptospira interrogans Isolates from Malaysia Reveals Massive Genome Rearrangement but High Conservation of Virulence-Associated Genes

Abstract: The ability of Leptospirae to persist in environments and animal hosts but to cause clinically highly variable disease in humans has made leptospirosis the most common zoonotic disease. Considering the paucity of data on variation in complete genomes of human pathogenic Leptospirae, we have used a combination of Single Molecule Real-Time (SMRT) and Illumina sequencing to obtain complete genome sequences of six human clinical L. interrogans isolates from Malaysia. All six contained the larger (4.28–4.56 Mb) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…2.0. g-tubes TM from Covaris (Woburn, MA, USA) was used to shear 1 g of genomic DNA, and AMPure PB beads from Pacific Bioscience were used to concentrate the DNA. The DNA was finally repaired following an overnight ligation to an affixed barcoded 8A adaptor (Pacific Bioscience) [ 4 , 5 ]. The size selection instructions provided by the manufacturer, Sage Science, Beverly, Massachusetts, USA, for Blue Pippin TM 4 kb or more were adhered to.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…2.0. g-tubes TM from Covaris (Woburn, MA, USA) was used to shear 1 g of genomic DNA, and AMPure PB beads from Pacific Bioscience were used to concentrate the DNA. The DNA was finally repaired following an overnight ligation to an affixed barcoded 8A adaptor (Pacific Bioscience) [ 4 , 5 ]. The size selection instructions provided by the manufacturer, Sage Science, Beverly, Massachusetts, USA, for Blue Pippin TM 4 kb or more were adhered to.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…During the last decade, research work targeting the pathogenesis mechanism of leptospirosis has seen an upsurge in the identification of components involved in the adhesion, colonization, immune evasion, and establishment of pathogens in the host system. Even though the complete genome is available for many pathogenic and non-pathogenic strains (Ramli et al 2021 ; Vincent et al 2019 ; Thibeaux et al 2018 ) and many studies comparing the genomes are published, a clear picture of the pathogenesis mechanism is not available. In Leptospira , as per the current data, nearly 10 proteins were found to act on the cell junction proteins of the host system and play a role in the invasion/colonization process (Evangelista et al 2014a , b ; Eshghi et al 2019 ; Pinne et al 2010 and many more).…”
Section: Cell Junction Disrupter Orthologs In Leptospira ...mentioning
confidence: 99%
“…LipL32 is also highly conserved in pathogenic, and it is expressed during infection. Ramli et al [53] concluded that L. interrogans is a dynamic pathogen and there are still many virulence features to be discovered.…”
Section: Genome Features In Pathogenic Leptospiresmentioning
confidence: 99%